International degree mobility in library and information science (Libellarium: journal for research in the field of information and related sciences, 2017)
This study examines whether a brain drain exists in LIS and explores the patterns of geographical mobility of researchers. Brain drain or brain gain describes the migration of scientists from their home country to another. The results are based on a quantitative dataset of 877 active LIS researchers who have been involved in the 2014 to 2016 iConferences. The study reveals two alarming trends: the American LIS researchers rarely ever leave their continent and might lack international exposure. On the other hand, researchers from Asia and Europe show a high rate of mobility towards North America. In particular, the next generation of LIS researchers are currently receiving their education in North America. 94.3 % of all PhD students in the sample currently live in the US and may never return. One important pull factor seems to be the possibility of studying in English. If foreign students decide to come to Europe, they go to Ireland or the United Kingdom.
Keywords: mobility; education; LIS; brain drain; lingua franca